Effect of Au Nanoparticles and Scattering Layer in Dye-Sensitized Solar Cells Based on Freestanding TiO2 Nanotube Arrays - Kang-Hun Lee; Seung-Hee Han; Ana Chuquer; Hwa-Young Yang; Jaehi Kim; Xuan-Hung Pham; Won-Ju Yun; Bong-Hyun Jun; Won-Yeop Rho (Nanomaterials, 2021)
The development of high efficiency dye-sensitized solar cells (DSSCs) has received tremendous attention. Many researchers have introduced new materials for use in DSSCs to achieve high efficiency. In this study, the change in power conversion efficiency (PCE) of DSSCs was investigated by introducing two types of materials—Au nanoparticles (Au NPs) and a scattering layer. A DSSC fabricated without neither Au NPs nor a scattering layer achieved a PCE of 5.85%. The PCE of a DSSC based on freestanding TiO2 nanotube arrays (f-TNTAs) with Au NPs was 6.50% due to better electron generation because the plasmonic absorption band of Au NPs is 530 nm, which matches the dye absorbance. Thus, more electrons were generated at 530 nm, which affected the PCE of the DSSC. The PCE of DSSCs based on f-TNTAs with a scattering layer was 6.61% due to better light harvesting by scattering. The scattering layer reflects all wavelengths of light that improve the light harvesting in the active layer in DSSCs. Finally, the PCE of DSSCs based on the f-TNTAs with Au NPs and a scattering layer was 7.12% due to the synergy of better electron generation and light harvesting by plasmonics and scattering. The application of Au NPs and a scattering layer is a promising research area for DSSCs as they can increase the electron generation and light harvesting ability.